Behaviour of the main okra (Abelmoschus spp.) cultivars grown in Côte d’Ivoire to root-knot nematodes (Meloidogyne incognita (Kofoid and White, 1919)) under greenhouse conditions - Yadom Yao François Regis KOUAKOU; Kouamé Daniel KRA; Marie Noel Yeyeh TOUALY; Bognan Miyasi Winnie OUATTARA; Kouamé Clément DJEZOU; Hortense ATTA DIALLO (Acta Agriculturae Slovenica)
Root-knot nematodes are the main factor limiting okra production in Côte d’Ivoire. Using resistant cultivars appears to be one of the best strategies for managing root-knot nematodes. The aim of this study was to determine the behaviour of the main okra cultivars grown in Côte d’Ivoire against Meloidogyne incognita. Seeds of 20 okra cultivars were planted in pots under greenhouse conditions. Fourteen-day-old plants of okra cultivars were inoculated with 500 second-stage juveniles of M. incognita. Agronomic and pathological parameters were determined. The Basanti cultivar exhibited the highest gall index (5.0/plant), final population (7938 individuals/plant), and reproductive factor (15.88/plant) of M. incognita, whereas the Hiré cultivar showed one of the lowest gall indexes (3.0/plant), final population (912 individuals/plant), and reproductive factor (1.8/plant). Two groups of cultivars were identified based on their susceptibility to M. incognita and their agronomic performance. One group consisted of cultivars that were less susceptible to M. incognita and had better agronomic performance. Cultivars that were more susceptible to M. incognita and had poorer agronomic performance made up the other group. The Hiré cultivar was the least favourable to M. incognita development. Based on the current study, the Hiré cultivar may be a promising option for farmers in root-knot nematode-prone environments.